Non-finites - Ylikoski Jussi (Oxford University Press, 2023)
This is the first English-language description of Lule Saami, an indigenous language spoken in Norway and Sweden. With nearly one thousand speakers, Lule Saami is the second most spoken Saami language. However, outside Saami linguistics it is often overshadowed by its immediate neighbour North Saami, the numerically strongest and best known Saami language that is often used to represent the whole Saami branch. While the general make-up of Lule Saami is in many ways similar to that of North Saami, it also has a number of features shared with other western Saami languages but lacking in North Saami. These features include nominal inflection with as many as eight morphological cases and the negative verb that is inflected in not only number (singular, dual, plural) and person, but also in tense. With its relatively free word order, Lule Saami has an intermediate position between North Saami (SVO) and South Saami (SOV).
The Oxford Guide to the Uralic Languages